Age-related changes in motor control during articulator visuomotor tracking. - Ballard, Kirrie J.; Robin, Donald A.; Woodworth, George (Journal of Speech, Language & Hearing Research, 2001)
The present study provides normative data on changes in visuomotor control of the oral-facial system across the lifespan. Control of the lower lip, jaw, and larynx (i.e., fundamental frequency) was examined using a nonspeech visuomotor tracking (VMT) task, where subjects move the articulator of interest to track a moving target on an oscilloscope screen. This task examines articulator motor control during movements that are similar to speech but that do not impose linguistic units or the demands of coordinating multiple structures. Accuracy and within- and between-subject variability in tracking performance were measured by cross correlation, gain ratio, phase shift, and target-tracker amplitude difference. Cross-correlation analyses indicated that performance of children (aged 8;2 to 17;0 {years;months}) and older adults (aged 45;1 to 84;3) is poorer than that of younger adults (aged 17;1 to 45;0). Accuracy of movement amplitude tended to increase during development and decline with aging, whereas age did not appear to influence accuracy of temporal parameters in lip and jaw tracking. In contrast, age tended to influence individual variability in temporal but not amplitude parameters. Differences were noted between articulators. The data complement previous studies that considered accuracy and variability of articulator movement during speech. The VMT method and the data provided may be applied to assessment of impairments in the motor speech system and to differential diagnosis of motor speech versus linguistically based disorders. Reprinted by permission of the publisher.